A review of disparities in access to infertility care and treatment outcomes among Hispanic women - Allison S. Komorowski; Tarun Jain (BMC, 2022)
Abstract Hispanic women have lower rates of use of infertility services than non-Hispanic White women. There are many barriers that impede access to infertility care including economic, geographic, cultural, and societal factors and there are disparities in treatment outcomes. Hispanic women are less likely to seek infertility care than non-Hispanic White women and even after infertility evaluation, Hispanic women are less likely to receive treatment for their infertility. Lower use of infertility treatments among Hispanic women is unlikely to be driven solely by economic factors. There is disappointingly little data on in-vitro fertilization treatment outcomes including the population of Hispanic women, and existing data has yielded conflicting results. Incomplete and variable reporting of race data across clinics raises the potential for misclassification bias and invalid study conclusions. Addressing disparities in access to reproductive medicine in the Hispanic population will required a multifaceted approach including expanded insurance coverage, improved education for both patients and providers, and additional research on barriers to care.